Speech Impairment in a Large Sample of Patients with Parkinson’s Disease - Aileen K. Ho; Robert Iansek; Caterina Marigliani; John L. Bradshaw; Sandra Gates (Behavioural Neurology)
This study classified speech impairment in 200 patients with Parkinson’s disease (PD) into five levels of overall severity and described the corresponding type (voice, articulation, fluency) and extent (rated on a five-point scale) of impairment for each level. From two-minute conversational speech samples, parameters of voice, fluency and articulation were assessed by two trained-raters. Voice was found to be the leading deficit, most frequently affected and impaired to a greater extent than other features in the initial stages. Articulatory and fluency deficits manifested later, articulatory impairment matching voice impairment in frequency and extent at the ‘Severe’ stage. At the final stage of `Profound' impairment, articulation was the most frequently impaired feature at the lowest level of performance. This study illustrates the prominence of voice and articulatory speech motor control deficits, and draws parallels with deficits of motor set and motor set instability in skeletal controls of gait and handwriting.